The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12199-018-0760-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental extreme temperature and daily preterm birth in Sabzevar, Iran: a time-series analysis

Abstract: ObjectivesMost of the studies on the effect of heat stress on preterm birth (PTB) are conducted in temperate climates. Evidence on this effect in hot and arid countries with low and middle income is limited. This paper describes the short-term effect of exposure to the hot and cold environment on a daily number of PTB in Iran.MethodsThe daily number of PTB was obtained from all hospitals of the city. Meteorological and air pollution data from 2011 to 2017 were obtained from a metrological station in the city. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(49 reference statements)
1
30
0
Order By: Relevance
“…For example, a study from Guangzhou, China reported that extreme heat and extreme cold during the last 4 weeks of pregnancy increased the risk of preterm birth by 17.9% and 10%, respectively [ 51 ]. Likewise, in Sabzevar, Iran, both very hot and very cold temperatures were associated with an increase in PTL [ 52 ]. Li et al [ 53 ], in Brisbane, showed that during the years under study (1993–2013), the effect of low temperature was stronger than the effect of high temperature for preterm delivery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study from Guangzhou, China reported that extreme heat and extreme cold during the last 4 weeks of pregnancy increased the risk of preterm birth by 17.9% and 10%, respectively [ 51 ]. Likewise, in Sabzevar, Iran, both very hot and very cold temperatures were associated with an increase in PTL [ 52 ]. Li et al [ 53 ], in Brisbane, showed that during the years under study (1993–2013), the effect of low temperature was stronger than the effect of high temperature for preterm delivery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies calculated weekly, monthly, and trimesterspecific exposure temperatures based on daily temperature measurements. Nine studies employed apparent temperature (combined effect of air temperature and relative humidity) to identify the exposure effects on elevated ambient temperatures on pregnant women and neonates [11,12,[32][33][34][35][36][37][38]. Twelve studies examined the effects of heatwaves/extreme heat events on maternal, foetal, and neonatal outcomes [6,32,[38][39][40][41][42][43][44][45][46][47].…”
Section: The Magnitude Characteristics and Trends Of Research On Elev...mentioning
confidence: 99%
“…However, the risk of infectious diseases has always been affected by multiple factors, such as climate, the regional economy and environmental health. The impacts of meteorological factors on diseases, especially infectious diseases, are of particular current concern to researchers, and relevant studies have been comprehensive [5][6][7][8][9][10]. Numerous studies have concluded that BD transmission might be influenced by meteorological factors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%